(untitled) (MAGNETON: Jurnal Inovasi Pembelajaran Fisika, 2026)
Technological developments have brought significant changes in the field of education. The use of less varied media can lead to low student motivation, unfavorable classroom conditions, and a lack of teacher ability to adapt to digital media. This study aims to measure the effectiveness of using digital learning videos in increasing science learning motivation among elementary school students. A quasi-experimental study with a non-equivalent group design, conducted from September 2024 to March 2025. The research was conducted at MI Ma’arif Bego, Depok, Maguwoharjo, Sleman, Yogyakarta. The research subjects were selected using purposive sampling, consisting of two classes, namely class III B as the experimental class with 28 students, consisting of 13 boys and 15 girls, and class III C as the control class with 28 students, consisting of 14 boys and 14 girls. The data collection technique used a questionnaire guideline, with an instrument in the form of a questionnaire sheet (closed questionnaire). The data were analyzed using the SPSS 21 application, with an independent sample t-test and N-gain score. The results showed that the use of digital video learning media was quite effective in increasing student learning motivation in Madrasah Ibtidaiyah, with an independent sample t-test score of Sig. (2-tailed) of 0.000 < 0.05 and an average N-gain score percentage of 56.10%. The results of this study are expected to be used as a reference by teachers in planning effective learning to increase student motivation.